2020
DOI: 10.1016/j.cej.2019.122605
|View full text |Cite
|
Sign up to set email alerts
|

Designing efficient TiO2-based photoelectrocatalysis systems for chemical engineering and sensing

Abstract: Photoelectrocatalysis (PEC) incorporates electrochemical techniques with photocatalysis (PC) to facilitate the separation of the photoelectron-hole produced at semiconductor nanoparticles, leading to enhanced photocatalytic efficiency for various applications. Due to its inherently low cost, non-toxicity and chemical stability, titanium dioxide (TiO2) based PEC devices are considered the most promising system for chemical engineering such as pollution degradation and fuel generation, and PEC sensing. In an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 200 publications
(218 reference statements)
0
62
0
2
Order By: Relevance
“…This way, heterojunction promote the separation of photoexcited electron hole pairs through several carrier-transfer pathways by keeping reduction and oxidation reactions at two different reaction sites. Moreover, the coupled semiconductors can extend the light response range to the visible [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This way, heterojunction promote the separation of photoexcited electron hole pairs through several carrier-transfer pathways by keeping reduction and oxidation reactions at two different reaction sites. Moreover, the coupled semiconductors can extend the light response range to the visible [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that device design also plays a crucial role in improving the efficiency and reducing the cost of PC reactors [21][22][23]. A thin-layer reactor, which minimizes the thickness of the aqueous solution and the distance between the irradiation source and photocatalysts, is a promising device design for effective utilization of irradiation [24]. According to Beer's Law, light loss in aqueous solution is inevitable (Equation (7)):…”
Section: Introductionmentioning
confidence: 99%
“…Among these MOXs, TiO 2 is one of the most versatile ones and is widely used for many different applications, including photocatalysis [ 16 ], sensors [ 17 , 18 ] and photovoltaic applications [ 19 ]. In particular, due to its exceptional physical/chemical properties, TiO 2 was extensively used for different sensing applications such as chemical/gas sensors [ 20 , 21 ], biosensors [ 17 , 22 ] and chemical oxygen demand (COD) [ 23 , 24 ] sensors [ 25 ]. It typically exhibits n-type conductivity and, in nanostructured form, is chemically stable, biocompatible, biodegradable and inexpensive [ 25 ].…”
Section: Introductionmentioning
confidence: 99%